Downward wave reflection as a mechanism for the stratosphere–troposphere response to the 11-yr solar cycle - Lu, H; Scaife, A; Marshall, G; Turner, J; Gray, L (American Meteorological Society, 2017)
The effects of solar activity on the stratospheric waveguides and downward reflection of planetary waves during NH early to midwinter are examined. Under high solar (HS) conditions, enhanced westerly winds in the subtropical upper stratosphere and the associated changes in the zonal wind curvature led to an altered waveguide geometry across the winter period in the upper stratosphere. In particular, the condition for barotropic instability was more frequently met at 1 hPa near the polar-night jet centered at about 55°N. In early winter, the corresponding change in wave forcing was characterized by a vertical dipole pattern of the Eliassen–Palm (E–P) flux divergent anomalies in the high-latitude upper stratosphere accompanied by poleward E–P flux anomalies. These wave forcing anomalies corresponded with negative vertical shear of zonal mean winds and the formation of a vertical reflecting surface. Enhanced downward E–P flux anomalies appeared below the negative shear zone; they coincided with more frequent occurrence of negative daily heat fluxes and were associated with eastward acceleration and downward group velocity. These downward-reflected wave anomalies had a detectable effect on the vertical structure of planetary waves during November–January. The associated changes in tropospheric geopotential height contributed to a more positive phase of the North Atlantic Oscillation in January and February. These results suggest that downward reflection may act as a “top down” pathway by which the effects of solar ultraviolet (UV) radiation in the upper stratosphere can be transmitted to the troposphere.